Gender and Audit Score Sginificantly Interact to Effect Fluid Poured in a Simulated Alcohol Free Pour Task - Bakalars, Charles; Watson, Meredith; Hasenberg, Whitney; Matthews, Douglas (My University, 2016)
College students’ alcohol consumption isexcessive creating a potential public healthconcern (Van Skike et al., in press). Research has shown that college students will over pour a standard drink when participating in a simulated alcohol free pour task, creating the Overpour Effect (Zandy et al., 2013). This suggests that students self report alcohol use data may beincorrect. Interesting, and contrary to the Overpour Effect, previous research has also shown that subjects will pour less fluid in a simulated alcohol pouring task if they are asked to pour in the presence of an unfamiliar peer (Zandy et al., 2013). However, it is unknown what social factors in the interaction between the subject and the unfamiliar peer influence pouring behavior. This study investigates how gender of the subject and unfamiliar peer and previous alcohol use history interact to affect fluid poured in a simulated alcohol free pour task.
Color poster with text, images, and graphs.
Keywords: Gender; AUDIT; Barlett Impulsivity Scale; Posters; Alcohol consumption